No Benefit of Complex Fractionated Atrial Electrogram Ablation in Addition to Circumferential Pulmonary Vein Ablation and Linear Ablation: Benefit of Complex Ablation Study. (December 2015) - Wong, Kelvin C.K.; Paisey, John R.; Sopher, Mark; Balasubramaniam, Richard; Jones, Michael; Qureshi, Norman; Hayes, Chris R.; Ginks, Matthew R.; Rajappan, Kim; Bashir, Yaver; Betts, Timothy R.
Abstract : Background—: The optimal ablation strategy for persistent atrial fibrillation (AF) remains unclear. Methods and Results—: This multicentre randomized study compared circumferential pulmonary vein ablation+linear ablation (control arm) versus circumferential pulmonary vein ablation+linear ablation+complex fractionated atrial electrogram (CFAE) ablation (CFAE arm) in patients with persistent AF. Circumferential pulmonary vein ablation was performed followed by roof and mitral isthmus ablation, before CFAE ablation in the CFAE arm. Ablation strategy was maintained at the first redo procedure. Sixty-five patients were recruited in each arm. The mean age was 61±10 years, 75% were men, median AF duration was 2 years, 42% had long-lasting persistent AF, 68% had associated cardiovascular disease, mean left atrial dimension was 46±6 mm, and median CHA2 DS2 -VASc score was 2. Ablation and procedure times were significantly longer in the CFAE arm (70±20 versus 55±17; 201±35 versus 152±45 minutes; P <0.005). After a mean follow-up of 35±5 months, single-procedural success off antiarrhythmic drugs at 12 months (CFAE: 30/65 [46%] versus control: 37/65 [57%]; P =0.29) and multiprocedural success (CFAE: 51/65 [78%] versus control: 52/65 [80%]; P =1.0) were not significantly different. At the first redo procedure, patients in the CFAE arm had a higher incidence of organized atrial tachycardia/flutter (24/33 [73%] versus 11/31 [35%]; P =0.005) and gap-related macro–re-entrant flutter (8/33[24%] versus 1/31[3%]; P =0.03). Early recurrence of atrial arrhythmia was an independent predictor of late recurrence. Conclusions—: CFAE ablation did not confer incremental benefit when performed in addition to circumferential pulmonary vein ablation and linear ablation. It was associated with a higher incidence of gap-related flutter. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01711047. Abstract : Supplemental Digital Content is available in the text.